Validação do Questionário de Avaliação de Habilidades Sociais, Comportamentos, Contextos para Universitários - Bolsoni-silva, Alessandra Turini; Loureiro, Sonia Regina (Instituto de Psicologia, Universidade de Brasília, 2016)
ABSTRACT There is a lack of instruments to assess social skills in the interface with mental health of college students. This study intended to test the psychometric properties of validity and reliability of the Social Skills, Behaviors and Context Assessment Questionnaire for University Students (QHC - University Students). In a collective situation 609 university students from different courses were evaluated with the following instruments: QHC - College students, IHS-Del Prette, BDI, Mini-SPIN and SCID-IV. The psychometric properties were measured by statistical procedures, with satisfactory results concerning the internal consistency and construct validity and concurrent. Factor analysis isolated three factors for Part 1 (Communication and Affect, Coping, Public Speaking) and two factors for Part 2 (Potentialities and Difficulties), providing scores of problems and skills.

RESUMO Verifica-se uma carência de instrumentos que avaliem habilidades sociais na interface com a saúde mental de universitários. Objetiva-se testar as propriedades psicométricas de validade e fidedignidade do Questionário de Avaliação de Habilidades Sociais, Comportamentos e Contextos para Universitários - QHC-Universitários. Procedeu-se à avaliação, em situação coletiva, de 609 estudantes universitários de diferentes cursos por meio dos seguintes instrumentos: QHC-Universitários, IHS-Del Prette, BDI, Mini-SPIN e SCID-IV. As propriedades psicométricas foram aferidas por meio de procedimentos estatísticos, com resultados satisfatórios quanto à consistência interna e às validades de construto e concorrente. A análise fatorial isolou três fatores para a Parte 1 (Comunicação e Afeto, Enfrentamento, Falar em Público) e dois fatores para a Parte 2 (Potencialidades, Dificuldades), fornecendo escores de problemas e de habilidades.
Validation of the Social Skills, Behaviors and Context Assessment Questionnaire for University Students
Keywords: social skills; mental health; college students; measurement; habilidades sociais; saúde mental; estudantes universitários; medidas